Sumac (Rhus coriaria L.) essential oil composition and its antimicrobial effect on Salmonella typhimurium - B Radmehr (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2011)
Consumers' interest over natural preservatives and their application as food ingredients is growing, which encourage complementary researches on various natural antimicrobials such as plant essential oils. Sumac (Rhus coriaria L.), is a plant that is used as a flavouring agent in Iranian traditional foods. Therefore, in this study Sumac essential oil composition and antimicrobial activity was evaluated. Sumac ssential oil was extracted with distillation and analyzed by gas chromatography method. Antimicrobial effect of Sumac essential oil against Salmonella typhimurium, that is considers as one of important pathogen in food, was evaluated. Antimicrobial effect of essential oil was evaluated by measuring turbidity as a result of bacterial growth at a broth media by Bioscreen C instrument at 35°C. Result showed that the most important fraction of essential oil that may have antimicrobial effect is Caryophyllen. Although Sumac essential oil had bacteriostatic effect at low concentration of 30 ppm, it showed bactericidal activity at high concentration of 1000 ppm. It could be concluded that, Sumac essential oil by its antimicrobial fractions can be used to control the growth of Salmonella typhimurium in food stuff.